The hateful eight [videorecording (Blu-Ray + DVD)] - Tarantino, Quentin; Jackson, Samuel L.; Russell, Kurt; Leigh, Jennifer Jason, 1962-; Goggins, Walton, 1971-; Bichir, Demián, 1963-; Roth, Tim; Madsen, Michael, 1971-; Dern, Bruce; Parks, James, 1968-; Tatum, Channing; Morricone, Ennio; et al. (Anchor Bay Entertainment, 2016)
A stagecoach hurtles through the wintry Wyoming landscape. Bounty hunter John Ruth and his fugitive Daisy race toward the town of Red Rock, where Ruth will bring Daisy to justice. Losing their lead on the blizzard, they seek refuge at Minnie's, a stagecoach stopover on a mountain pass. When they arrive at Minnie's, they are greeted not by the proprietor but by four unfamiliar faces. As the storm overtakes the mountainside stopover, our travelers come to learn they may not make it to Red Rock.